Postinjection Normal Closure of Fractures as a Mechanism for Induced Seismicity. Issue 19 (4th October 2017) - Ucar, E.; Berre, I.; Keilegavlen, E.
Abstract: Understanding the controlling mechanisms underlying injection‐induced seismicity is important for optimizing reservoir productivity and addressing seismicity‐related concerns related to hydraulic stimulation in Enhanced Geothermal Systems. Hydraulic stimulation enhances permeability through elevated pressures, which cause normal deformations and the shear slip of preexisting fractures. Previous experiments indicate that fracture deformation in the normal direction reverses as the pressure decreases, e.g., at the end of stimulation. We hypothesize that this normal closure of fractures enhances pressure propagation away from the injection region and significantly increases the potential for postinjection seismicity. To test this hypothesis, hydraulic stimulation is modeled by numerically coupling flow in the fractures and matrix, fracture deformation, and matrix deformation for a synthetic reservoir in which the flow and mechanics are strongly affected by a complex three‐dimensional fracture network. The role of the normal closure of fractures is verified by comparing simulations conducted with and without the normal closure effect. Key Points: Normal closure of stimulated fractures after the termination of injection enhances postinjection seismicity Processes are strongly affected by the complex structure of three‐dimensional fracture networks Consistent with microseismic data analyses, our simulations show that seismic events occur at the rim of the stimulation region